Ralph Ellison Travels to Denmark: Invisible Man/Usynlig Mand and the World Location of American Literature - Rasmussen, Johs (American Studies in Scandinavia, 2023)
This essay argues that the Danish translation of Invisible Man (1952), Ralph Ellison’s prize-winning debut novel, offers a set of spatiotemporal coordinates with which the world location of postwar American literature can be mapped. By reconstructing how Invisible Man was received both in the United States and Denmark, I show that the evaluative criteria by which the novel was judged to be a valuable work of art breaks down the geographical delimitation of national literatures. To that effect, the construction of the author figure “Ralph Ellison” was contingent upon his fiction conforming to criteria of evaluation formalized by cultural institutions such as newspapers, universities, and literary prizes. These criteria were often derived from aesthetic principles associated with European modernism, and they come into full view in my reconstruction of Invisible Man’s publication and (Danish) translation history. I conclude that the residue of Invisible Man’s paratextual apparatus which has survived to this day, as well as the global connections this residue signifies, exposes the discursive construction of a nationally specific American literature as an ideological fiction, not a material fact.